Production potentials and economics of chickpea-rice based cropping system in Sylhet area (AEZ 20) (Bangladesh Journal of Agricultural Research, 2015)
Global food and feed demands have been projected to double in the 21st century, which will further increase the pressure on the use of land, water and nutrients. To increase food productivity, production potential and economic returns, improvement of cropping system may play a vital role in this regards. A study was conducted to determine the economic consequences of two cropping patterns viz., ICP: Improved Cropping Pattern (Chickpea-T.Aus-T.Aman) and FECP: Farmers Existing Cropping Pattern (Fallow-T. Aus-T. Aman) through incorporation of modern high yielding varieties and improved management practices for crop production at farmers' fields of Sylhet during three consecutive years 2009-10, 2010-11, and 2011-12, respectively. The experiment was laid out in randomized complete block design with six dispersed replications. The pooled data showed that the improved management practices for the pattern provided higher yield in T.Aus and T.Aman rice, respectively. The gross return and gross margin of ICP were higher compared to that of FECP with only 21% extra cost. The higher benefit cost ratio (2.20), rice equivalent yield (10.29 t/ha), production efficiency (27.36 kg/ha/day), land-use efficiency (91.32%) and sustainable yield index (0.41) indicated the superiority of the ICP over the FECP. Higher rice equivalent yield indicate that ICP is suitable in Sylhet region for increasing crop productivity and cropping intensity. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21991 Bangladesh J. Agril. Res. 39(3): 479-490, September 2014